Students Perceptions in Online Class Learning During the Covid-19 Pandemic - Dewi Surani; Hamidah Hamidah (International Journal on Advanced Science, Education, and Religion, 2020)
The article was to determine student perceptions in online learning. This research was conducted by survey method by giving questionnaires to 239 active students of Bina Bangsa University. Quantitative data were analyzed by descriptive statistics and qualitative data from open-ended questions to gain insight into student perceptions. The analysis shows that 80% of students are willing to take part in online learning, 62% of students claim online learning provides benefits, and 32% of students have difficulty understanding the material. In conclusion, the perception of students in online learning is relatively good with several obstacles that require improvement. So it is recommended that online learning should be planned, implemented, and evaluated in order to minimize problems and maximize the achievement of learning objectives An abstract should explain a brief, comprehensive summary of article contents; it allows readers to survey. Keywords: Student Perception, Online Learning, Covid-19 Pandemic